Efforts To Improve The Discipline Performance of The State Civil Apparatus at The Sorong City Secretariat - Fitri Yanti; Charis Christian; Sumarmo Sumarmo (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This study aims to analyze efforts to improve the disciplinary performance of the State Civil Apparatus (ASN) in the Sorong City Regional Secretariat through the approach of apparatus compliance, internal supervision, enforcement of disciplinary sanctions, and organizational work culture. The research uses a mixed methods method, namely a quantitative approach through the dissemination of a Likert scale questionnaire analyzed using descriptive statistics and correlation, as well as a qualitative approach through in-depth interviews with the Regional Secretary, Head of the Inspectorate, Head of BKPSDM, Head of Organization and Administration, and Head of the People's Welfare Section. The study's results show that organizational work culture and internal supervision are positively related to apparatus compliance. At the same time, the enforcement of disciplinary sanctions plays a supporting role in maintaining the consistency of ASN discipline. Qualitative findings reinforce that leadership examples, employee development, and technology-based monitoring systems are important factors in improving apparatus discipline. The study's implications indicate that improving ASN discipline requires an integrated approach that strengthens the supervision system, fosters employee development, and develops an organizational work culture oriented towards public services. The study's limitation is in the narrow scope of respondents in the Sorong City Regional Secretariat; therefore, further research is recommended to include more regional apparatus and employ more comprehensive statistical analysis to yield deeper results.